Global sourcing strategy and sustainable competitive advantage - Kotabe, Masaaki; Murray, Janet Y. (Industrial marketing management, 2004)
Global sourcing strategy has been one of the most hotly debated management trends in the last 20 years. In its early years, global sourcing was examined mostly from “in-house” development and procurement perspectives; and in the last several years, research focus has shifted to “outsourcing” activities. Along with this shift from internal to external focus on global sourcing, many researchers and business practitioners have applied a core competency argument to justify increased levels of outsourcing activities on a global basis. Although the beneficial aspects of outsourcing are assumed in most cases, no consensus exists in reality as to the effect of outsourcing. Furthermore, the increased instability of the exchange rate environment in the last several years has also led to increased difficulties in managing globally scattered operations that were once fashionable in the 1980s-90s under the rubric of global strategy. In this article, the authors explore potential limitations and negative consequences of outsourcing strategy on a global scale.